Structural Analysis of Cultural Hegemony in Shakespeare’s Othello - Kousar, Shazia (Journal of Research in Humanities, 2023)
: Parallel to language, cultures are made up of structures which departmentalize individuals into different categories. This study applies Saussure’s theory of structuralism on social structures of racism and gender exhibited in Shakespeare’s tragedy Othello. These cultural structures dictate the role of the characters, particularly, of the protagonists: Othello and Desdemona. The characters like signs are regulated and determined by the social structures prescribed by community. These social systems are arbitrary as there is no any logic of signifying Othello by his ‘blackness’ which further signifies ‘barbarism’ and ‘wildness’. Likewise, Desdemona is signified by ‘feminity’ approved by the collective inertia of Venetian society. This process of arbitrary signification makes the whole social structures arbitrary which protects them from any modification in community. The inflexible sign system in social structures leads to their rigidity and conservativeness. Any attempt of these characters to assert their autonomy makes them distrustful in the community which, eventually, causes their tragedy.